2022
DOI: 10.3389/fimmu.2022.821007
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin of Neutrophil Extracellular Traps in COVID-19

Abstract: Despite ongoing vaccination COVID-19 is a global healthcare problem because of the lack of an effective targeted therapy. In severe COVID-19 manifesting as acute respiratory distress syndrome, uncontrolled innate immune system activation results in cytokine deregulation, damage-associated molecular patterns release upon tissue damage and high occurrence of thrombotic events. These pathomechanisms are linked to neutrophil function and dysfunction, particularly increased formation of neutrophil extracellular tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 146 publications
0
24
0
Order By: Relevance
“…Upregulated genes of low ubiquitination were associated with negative cytokine‐mediated signalling regulation and positive neutrophil mediation regulation. Elevated neutrophils were concentrated in severe COVID‐19 patients, which could be attributed to the formation of neutrophil extracellular traps 43 …”
Section: Discussionmentioning
confidence: 99%
“…Upregulated genes of low ubiquitination were associated with negative cytokine‐mediated signalling regulation and positive neutrophil mediation regulation. Elevated neutrophils were concentrated in severe COVID‐19 patients, which could be attributed to the formation of neutrophil extracellular traps 43 …”
Section: Discussionmentioning
confidence: 99%
“…These circumstances can lead to lung epithelial destruction and death [ 392 ]. Thus, it has been suggested that the MPO-DNA complex should be further investigated as a biomarker for the early phase of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infection [ 393 , 394 ]. NETs could also potentially serve as biomarkers in other diseases, such as cancer.…”
Section: Potential Pathological Effects and Biological Functions Of C...mentioning
confidence: 99%
“…Cl-amidine was shown to inhibit NET release in both SARS-CoV-2- infected healthy neutrophils and blood neutrophils of COVID-19 patients ( 66 ). Sivelestat can improve lung function and oxygen saturation in patients with ARDS ( 209 ). A new generation of NE inhibitors (Lonodelestat, Alvelestat, CHF6333 and Elafin) is currently in clinical trials.…”
Section: Treatment Strategymentioning
confidence: 99%